Effect of Different Physical Cross-Linkers on Drug Release from Hydrogel Layers Coated on Magnetically Steerable 3D-Printed Microdevices - Roberto Bernasconi; Fabio Pizzetti; Arianna Rossetti; Riccardo Perugini; Anna Nova; Marinella Levi; Filippo Rossi (Technologies, 2021)
In the last few decades, the introduction of microrobotics has drastically changed the way medicine will be approached in the future. The development of untethered steerable microdevices able to operate in vivo inside the human body allows a high localization of the therapeutical action, thus limiting invasiveness and possible medical complications. This approach results are particularly useful in drug delivery, where it is highly beneficial to administer the drug of choice exclusively to the target organ to avoid overdosage and side effects. In this context, drug releasing layers can be loaded on magnetically moveable platforms that can be guided toward the target organ to perform highly targeted release. In the present paper, we evaluate the possible application of alginate hydrogel layers on moveable platforms manufactured by coupling additive manufacturing with wet metallization. Such alginate layers are reticulated using three different physical crosslinkers: Ca, Zn or Mn. Their effect on drug release kinetics and on device functionality is evaluated. In the case of alginate reticulated using Mn, the strongly pH dependent behavior of the resulting hydrogel is evaluated as a possible way to introduce a triggered release functionality on the devices.